Modelling the System of Ensuring the Investment Security - Moroz Maxim O. (Bìznes Inform, 2017)
The article explores approaches to modelling the system of ensuring the investment security. Necessity of observance of investment security of Ukraine has been substantiated. The author’s own vision of the modelling essentials has been provided. The eligibility for consideration of the system of ensuring the investment security of Ukraine in the functional, structural, process, formative, and factor aspects has been proved. The target setting and tasks of a functional model of the system of ensuring the investment security have been defined. The functions, subjects, organizational-economic mechanisms of the system of ensuring the investment security of Ukraine have been characterized. A structural model of the system of ensuring the investment security has been presented. Special attention has been given to the definition of objects of direct and indirect influence, control and controlled subsystems, aggregate of indicators, safe levels, principles of formation of the investment security system. The process and formative models of the system of ensuring the investment security, as well as the algorithm of the complex assessment of the level of investment security, were analyzed in detail. Measures to ensure the investment security of Ukraine have been defined.